Trigonometry problem.
in Trigonometry Answers by

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

2 Answers

C=180-(A+B) so cosC=-cos(A+B), sinC=sin(A+B) and tanC=-tan(A+B).

But cosA=cosBcosC=-cosBcos(A+B), so sinA=sqrt(1-cos^2A)=sqrt(1-cos^Bcos^2(A+B)).

cos(A+B)=cosAcosB-sinAsinB, sin(A+B)=sinAcosB+cosAsinB, tan(A+B)=(tanA+tanB)/(1-tanAtanB); cos2B=2cos^2B-1, cos^2B=(cos2B+1)/2; sin2B=2sinBcosB (standard trigonometric identities).

Let cosA=a and cosB=b, so a=-b(ab-sqrt((1-a^2)(1-b^2)))=-ab^2+bsqrt((1-a^2)(1-b^2)).

a(1+b^2)=bsqrt((1-a^2)(1-b^2)); squaring both sides: a^2(1+b^2)^2=b^2(1-a^2)(1-b^2);

)a^2+2a^2b^2+a^2b^4=b^2(1-a^2-b^2+a^2b^2)=b^2-a^2b^2-b^4+a^2b^4;

a^2+3a^2b^2=b^2-b^4; a^2=b^2(1-b^2)/(1+3b^2) and a=bsqrt((1-b^2)/(1+3b^2)), so we have a in terms of b. We can also write: cosA=cosBsinB/sqrt(1+3cos^2B)=sin2B/2sqrt(1+(3/2)(cos2B+1))=sin2B/sqrt(10+6cos2B).

From this sinA=sqrt(1-sin^2(2B)/(10+6cos2B))=sqrt((10+6cos2B-sin^2(2B))/(10+6cos2B))

=sqrt((10+6cos2B-1+cos^2(2B))/(10+6cos2B))=sqrt((9+6cos2B+cos^2(2B))/(10+6cos2B))=

(3+cos2B)/sqrt(10+6cos2B), and tanA=sinA/cosA=(3+cos2B)/sin2B=3cosec2B+cot2B.

Also, tanA=sinA/cosA=sqrt(1-a^2)/a; tanB=sqrt(1-b^2)/b; tanC=(sqrt(1-a^2)/a+sqrt(1-b^2)/b)/(1-sqrt((1-a^2)(1-b^2))/ab)=(bsqrt(1-a^2)+asqrt(1-b^2))/(ab-sqrt((1-a^2)(1-b^2))).

Or, tanC=(3cosec2B+cot2B+tanB)/(1-(3cosec2B+cot2B)tanB).

tanA-tanB-tanC=(bsqrt(1-a^2)-asqrt(1-b^2))/ab-(bsqrt(1-a^2)+asqrt(1-b^2))/(ab-sqrt((1-a^2)(1-b^2)))

=tanA-tanB+tan(A+B)=tanA-tanB+(tanA+tanB)/(1-tanAtanB)

=(tanA-tanB-(tanA-tanB)tanAtanB+tanA+tanB)/(1-tanAtanB)=(2tanA-(tanA-tanB)tanAtanB)/(1-tanAtanB)

=tanA(2-tanB(tanA-tanB)tanB)/(1-tanAtanB).

tanA-tanB-tanC=3cosec2B+cot2B-tanB-(3cosec2B+cot2B+tanB)/(1-tanB(3cosec2B+cot2B))=

(-2tanB-tanB(3cosec2B+cot2B)(3cosec2B+cot2B-tanB))/(1-tanB(3cosec2B+cot2B).

[This is the same as:

sin(A-B)/cosAcosB-sin(A+B)/cos(A+B)=(sin(A-B)cos(A+B)-sin(A+B)cosAcosB)/(cosAcosBcos(A+B)).

The question doesn't specify in what terms tanA-tanB-tanC is to be expressed. tanA and tanB are mutually dependent values, but tanC depends on angles A and B. For example, tanB and tanC can both be expressed in terms of A, tanA and tanC can both be expressed in terms of B, etc. Similarly, tanA-tanB-tanC can be expressed in A, or B, or C.]

More...

 

by Top Rated User (695k points)
Prouve TanB=(b×sinC)/(a-b×cos). B and C are the angles a and b the distances
by

Related questions

1 answer
1 answer
Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
84,102 questions
89,036 answers
1,992 comments
6,728 users